Temporal and spatial variation of crown condition of main Norway spruce and oak species - Volker Mues (Federal Research Centre for Forestry and Forest Products (BFH), Institute for World Forestry, 2003)
The aim of this Internal Report is to analyse the spatial and temporal development of defoliation for Norway spruce (Picea abies) as well as for European and Sessile oak (Quercus robur and Q. petraea) in Europe by means of the transnational Level I data set of ICP Forests and the European Union's 'Scheme on the Protection of Forests against Atmospheric Pollution'. Additional external deposition and meteorological data are used to describe the influence of single stress factors. According to the methodology published in LORENZ et al. (2002) the medium term mean defoliation is used to describe the spatial variability whereas the plot and year specific differences to the medium term mean are used to describe the temporal variability. Possible refinements of the methodology are outlined as well. In line with expectations the analyses of the spatial variability of Norway spruce and oak species show significant correlations of insects, age and country with annual mean defoliation. In general, the deposition of sulphur was positively correlated with medium term mean defoliation. The models revealed no consistent results for the nitrogen components but nitrate deposition was significant in the model for Norway spruce with negative regression coefficients. The index for fungi infestation was negatively correlated with medium term mean defoliation of oak species. This was not expected from the understanding of fungi as damaging effect but was also found for beech (Fagus sylvatica) in earlier evaluations (LORENZ et al. 2002). The index for insect pests was significant in the models for Norway spruce as well as for oak. Additionally, plausible but not significant correlations were found with precipitation. Time trends were mapped for Norway spruce and oak species as a description of the mean development in the evaluation period. The analyses of the temporal variation of defoliation for Norway spruce and oak will be carried out for the Technical Report Level I 2003. Additionally, alternative methods and amendments to the method published by LORENZ et al. (2002) will be tested.
urn:nbn:de:gbv:253-201002-dk040079-3
Keywords: 630